Carbon Nanotubes Reinforced Copper Matrix Nanocomposites via Metal Injection Molding Technique - ., Ali S Muhsan, Faiz Ahmad, Norani M Mohamed, Putri SMBTM Yusoff, (2012)
New thermal management solutions are required to provide cost-effective means of dissipating heat from next generation microelectronic devices. In this paper, fabrication of heat sink nanocomposite made of copper reinforced by multiwalled carbon nanotubes up to 10 Vol.% using metal injection molding technique is presented. A mixture of Cu-MWNTs was compounded using internal mixer machine for homogenous dispersion of the solid powder in the binder.